1987
DOI: 10.1021/es00161a010
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air pollution due to emissions from wood-burning stoves

Abstract: Wood-burning stoves can emit pollution indoors during starting, stoking, and reloading operations. They can also emit pollution indoors if they are not airtight or are malfunctioning. Four woodburning stoves, three airtight and one non-airtight , were operated in a single-floor 236-m 3 residence and tested for pollutant emissions. Results showed the airtight stoves emitted small "puffs" of carbon monoxide and respirable suspended particles during door-opening operations while the non-airtight stove continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 12 publications
6
40
0
Order By: Relevance
“…One possible mechanism describes increased production of asthma symptoms as the result of localized airway inflammation produced by increases in lung tissue toxins or airborne allergens (15). Experimental studies have demonstrated that household environmental tobacco smoke (ETS) and stove exhaust are sources of air pollutants detrimental to human lung function, such as nitrous oxide (16), carbon monoxide, and respirable particles (17,18).…”
mentioning
confidence: 99%
“…One possible mechanism describes increased production of asthma symptoms as the result of localized airway inflammation produced by increases in lung tissue toxins or airborne allergens (15). Experimental studies have demonstrated that household environmental tobacco smoke (ETS) and stove exhaust are sources of air pollutants detrimental to human lung function, such as nitrous oxide (16), carbon monoxide, and respirable particles (17,18).…”
mentioning
confidence: 99%
“…If (25,(29)(30)(31)(32)(33)(34) Table 7 provides similar data for the main compounds found in the particulate phase of tobacco smoke (40).…”
Section: Case Study: Past and Present State Program Prioritiesmentioning
confidence: 97%
“…However, even the most efficient WBS emit some hazardous pollutants directly into the home when the stove is operating and the door is opened to add wood (25,(29)(30)(31)(32)(33)(34). This issue is especially important when one considers the trend to increase home insulation and overall airtightness in an effort to conserve energy and reduce heat loss (27).…”
Section: Case Study: Past and Present State Program Prioritiesmentioning
confidence: 99%
“…The fine particle deposition rate used was 0.08 h-l and is based on combustion products horn a wood-burning stove in a test house (Traynor et al 1987). The coarse particle deposition rate used was 1.5 h-*and is based on the lower value reported for 4~m particles in a test room (Byrne et al 1993).…”
Section: Pollutant Factorsmentioning
confidence: 99%